Pengaruh Penerapan Strategi Pelaksanaan untuk Risiko Perilaku Kekerasan pada Pasien Gangguan Jiwa di Rumah Sakit Jiwa Aceh - Nabila Shalehah; Urip Pratama; Syarifah Masthura (Inovasi Kesehatan Global, 2025)
The incidence of violent behavior among mental health patients globally reaches 9%. One of the independent interventions carried out by nurses is the application of implementation strategies for patients with violent behavior tendencies, whose risk level is greater than that of other patients. This study aims to analyze the effect of implementation strategies on the risk of violent behavior in patients with mental disorders at the Aceh Mental Hospital. The implementation strategy consists of four main techniques: building trust, training in controlling violent behavior through medication, training in social/verbal risk control, and training in spiritual control. The study used a quasi-experimental design with a one-group pretest-posttest approach. A total of 2,166 inpatients at risk of violent behavior were identified over a one-year period, and 10 respondents were selected as samples using purposive sampling based on inclusion criteria. The research instrument was the BPAQ questionnaire, with aggression assessment ranging from low to very high. The results showed that the pretest average for signs and symptoms was 38.40, while the posttest score decreased to 11.60 after the implementation strategy intervention. Data analysis was performed using univariate and bivariate methods, with a paired t-test yielding a p-value of 0.000 (less than 0.05). This study concluded that the implementation strategy had a significant impact in reducing the risk of violent behavior in patients. It is recommended that patients' understanding of the implementation strategy therapy be continuously improved as an effort to control violent behavior.